How the kinetic behavior of organic chickens affects productive performance and blood and meat oxidative status: a study of six poultry genotypes - Mattioli, Simona (Poult Sci, 2021)
The aim of this study was to analyze the relationship between the kinetic behavior, carcass characteristics, oxidative status (blood and meat), and meat fatty acid profiles of 6 organically reared slower growing chicken genotypes (SrG). One hundred male chickens of 6 SrG were used: Ranger Classic (RC), Ranger Gold (RG), Rowan Ranger (RR), RedJA (RJ), CY Gen 5 JA87 (CY), and M22 × JA87 (M). Twenty chickens/genotype were selected to analyze behavior, while, 15 individuals were slaughtered and different traits were analyzed in the blood and drumstick meat. The variables were grouped into different principal components: kinetic activity (PC1, with explorative attitude as the highest score), productive performance (PC2, carcass and head/feet yields), blood (PC3, carbonyls, and TBARS) and meat (PC6, thiols, and TBARS) markers, technological traits (PC4, pH, and color), proximate meat composition (PCA5, moisture, lipids, protein, and ash), fatty acid profile, and nutritional indexes (PC7, IP, and PUFAn-3). Uni- and bivariate analyses showed a strong positive association between kinetic behaviors and blood and meat oxidation and a medium positive association with fatty acid profile and nutritional indexes, whereas a negative association was found between productive performance loads and the technological traits of meat. Generalized linear models showed that all PCs were influenced by genotype. In particular, CY and M resulted as less active genotypes; conversely, RR showed more kinetic activity, whereas RJ, RG, and RC exhibited intermediate levels of activity. Cluster analysis of kinetic behavior and blood or meat oxidative status highlighted 2 groups: nonwalking (NW: CY and M) and walking (W: RC, RG, RR, and RJ) animals. However, in the W group, another was visualized, constituted by genotypes with high kinetic activity resulting in the worst oxidative balance (Walking not trained-genotypes, Wnt: RR and RJ). The present results confirmed that the kinetic behavior of SrG genotypes is negatively correlated with productive performance. Furthermore, a significant association between kinetic behavior and blood (positively correlated) or meat (negatively correlated) oxidative status was noted. Such differences are mainly due to the intrinsic response of the genotypes used (i.e., training-walking capacity).